Oyun oynama bozukluğu ölçeği – ebeveyn formu'nun geliştirilmesi / Development of the "gaming disorder scale – parent form" - ERTAŞ, Erdem (Bezmialem Vakıf University, 2020)
Gaming disorder is an important public health concern that mostly seen among children and adolescents. The impairing effects of this phenomenon have been documented in several studies. However, the measurement tools that help to evaluate in clinical environment are insufficient. The main goal of this study is to develop a valid and reliable psychometric measurement tool adopted in Turkish culture, which enables evaluating the gaming disorder symptoms of the children and adolescents by their parents. 750 parents with a child aged between 6-18 (11.7 ± 3.44) participated in our study through an online questionnaire. With the purpose of validity study, the sample was divided into two parts; exploratory factor analysis (EFA) was applied for 380 participants, and confirmatory factor analysis (CFA) was applied for 370 participants. For the reliability analysis, test-retest analysis and internal consistency were investigated. As a result of the EFA, in conformance with the ICD-11 Gaming Disorder diagnosis criteria, it was monitored that the 15-item scale includes three sub-dimensions (impaired control, increase in precedence, negative results) and this structure was confirmed with the CFA. According to these results, it was proved that Gaming Disorder Scale - Parental Form is a valid an reliable measurement tool. Gaming Disorder Scale – Parent Form that is based on the criteria of ICD-11 Gaming Disorder is a valid and reliable scale in Turkish culture. The scale allows parents to evaluate the gaming disorder symptoms of their children aged between 6 and 18. It is thought that this scale will contribute to the clinical evaluation process and research of the gaming disorder.
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Child and Adolescent Mental Health and Diseases, Istanbul, 2020
Keywords: Department of Child and Adolescent Mental Health and Diseases; Çocuk ve Ergen Ruh Sağlığı ve Hastalıkları Anabilim Dalı; Psikiyatri = Psychiatry; Güvenilirlik ve geçerlilik = Reproducibility of result; Psikolojik ölçekler = Psychological scales; Video oyunları = Video games